2019
DOI: 10.1039/c8cp05644g
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of protein–protein dissociation by statistical potential and coarse-grained simulations: a case study on interactions between colicin E9 endonuclease and immunity proteins

Abstract: A coarse-grained simulation method and a knowledge-based potential were developed to explore the dissociation mechanisms of protein complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In addition to the physics-based potential used in our original simulation method, we further introduced a statistics-based potential that was derived from analyzing the available protein complexes in the current structural database [ 74 ]. In detail, it has the following form: …”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the physics-based potential used in our original simulation method, we further introduced a statistics-based potential that was derived from analyzing the available protein complexes in the current structural database [ 74 ]. In detail, it has the following form: …”
Section: Model and Methodsmentioning
confidence: 99%
“…We further reduced the sequence redundancy from this database, which led to a final library consisting of 4960 entries of protein-protein interactions. The detailed procedure of extracting the energy parameters was described in our previous study [74].…”
Section: A Hybrid Force Field Of Intermolecular Interactions For Guidmentioning
confidence: 99%
“…In detail, Brownian dynamics algorithm was first used to drive the diffusions for all molecules in each time step of simulations by updating their Cartesian coordinates and velocities (34,35). The periodic boundary conditions are imposed.…”
Section: Methodsmentioning
confidence: 99%
“…27 With the RMSF value being ≤4.0 Å, a stable molecular complex can trigger fluctuating residues that contribute to receptor response activity. 28 The results showed that the conserved region consists of Asp30 & Arg26 from peptide B5 that binds to H chain BCR with hydrogen bonds. It initiates biological responses activation with residues stable binding of Lys43 and Val114 through hydrogen bonds interaction.…”
Section: Table 2 Vaccine Properties Of B-cell Epitopementioning
confidence: 98%